(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical characteristics and evaluate the local treatment outcomes of chronic atopic dermatitis using Ceradan cream compared to E-PSORA cream (PHAs, jojoba oil, vitamin E) at Can Tho Dermatology Hospital and the International Institute of Cosmetic Dermatology FOB from 2022 to 2024. Material and methods: A cross-sectional descriptive study was conducted on 88 chronic atopic dermatitis patients in 4 weeks at Can Tho Hospital of Dermatology and Venereology and FOB International Cosmetic Dermatological Institute in 2022-2024 Results: Most patients have moderate severity (77.2%) and common symptoms are itching (93.2%) and dry skin (80.7%). Ceradan and E-PSORA group both reach excellent and good treatment results after 4 weeks, however, the excellent result in the E-PSORA group were higher than the Ceradan group (63,6% and 13,6%) with p<0,001. Side effects have recongzed skin redness and itching which gradually increase with previous use of topical corticosteroids . Conclusion: Treatment of chronic atopic dermatitis with E-PSORA cream (PHA, jojoba e oil and vitamin E) achieves a better result than Ceradan cream.